Implementation of direct marketing in an effort to increase MICE customer loyalty - Fuadi, Farouk; Susanto, Budi; Aryana, I Nyoman Rajin (Journal of Commerce, Management, and Tourism Studies, 2022)
This research was conducted with the aim of identifying the implementation of direct marketing and analyzing the application of direct marketing in increasing customer loyalty. The theoretical foundation in this study uses relevant theories, namely regarding direct marketing and customer loyalty. Data collection was used by observation and interview methods which were processed using descriptive qualitative analysis techniques used to measure how well the implementation of direct marketing has been carried out and to analyze customer loyalty to the implementation of direct marketing that has been carried out. The results of this study state that the implementation of direct marketing is very important and has been carried out well by the marketing team. Where maintaining good relations with consumers and excellent service are the main factors for increasing customer loyalty.